1995
DOI: 10.1126/science.7539936
|View full text |Cite|
|
Sign up to set email alerts
|

Natural Protection Against HIV-1 Infection Provided by HIV-2

Abstract: Significant differences have been observed in the rates of transmission and disease development in human immunodeficiency virus (HIV) types 1 and 2. Because many HIV-2-infected people remain asymptomatic for prolonged periods, the hypothesis that HIV-2 might protect against subsequent infection by HIV-1 was considered. During a 9-year period in Dakar, Senegal, the seroincidence of both HIV types was measured in a cohort of commercial sex workers. Despite a higher incidence of other sexually transmitted disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
95
1
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 195 publications
(103 citation statements)
references
References 27 publications
4
95
1
1
Order By: Relevance
“…Whether these recombinant viruses are more prevalent in Progressors remains to be determined. Moreover, this suppressing activity of CD8 + cells might explain the suggested protection from HIV-I infection in previously HIV-2-infected individuals (Travers et al, 1995). It may also reflect the lack of simian in'tmunodeficiency virus pathogenicity in animal model systems in which prior infection with HIV-2 has occurred (Putkonen et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Whether these recombinant viruses are more prevalent in Progressors remains to be determined. Moreover, this suppressing activity of CD8 + cells might explain the suggested protection from HIV-I infection in previously HIV-2-infected individuals (Travers et al, 1995). It may also reflect the lack of simian in'tmunodeficiency virus pathogenicity in animal model systems in which prior infection with HIV-2 has occurred (Putkonen et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have shown that women infected with the relatively non-virulent HIV-2 are less susceptible than are uninfected cohorts to infection with HIV-1 (Travers et al, 1995). Chickens infected with herpesvirus of turkeys are protected from challenge with the virulent Marek's disease herpesvirus of chickens (Bu$ low, 1977 ;Okazaki et al, 1970 ;Purchase et al, 1972).…”
Section: Discussionmentioning
confidence: 99%
“…Coinfection of an individual does not invariably lead to recombination. For example, although naturally arising recombinants have been reported for HIV-2 (206, 315, 351), as have experimental recombinants between HIV-1 and HIV-2 (217), no natural HIV-1/HIV-2 recombinants have been reported (71,210) despite high rates of dual infection (327). Reasons for this may include limited cell coinfection and differences in RNA packaging (161,217,265).…”
Section: Rna Copackaging Determinants: Producer Cell Coinfectionmentioning
confidence: 99%